Implementation Of Zakat Funds For Educational Facilities And Infrastructure In The City Of Jayapura - Bintang Eka Saputry; Erni Mimin Indriani; Irham Renyaan; Marwa Fatkhurohmah; Jukri Baharuddin; Shimah Fauziah Yeubun (PAPUA: International Journal of Sharia Business Management, 2024)
The implementation of zakat funds for educational facilities and infrastructure in Jayapura City is a strategic step in improving access and quality of education for the local community. Education is very important for the development of human resources. In order to develop human resources, adequate facilies and infrastructure are needed to support the development process. One way to create adequate facilities and infrastructure is through the ese of zakat funds allocated for educational facilities and infrastructure. The results of the research show that it is permissible to channel zakat funds to build educational facilities and infrastructure, because it is part of the struggle in the way of Allah (fisabillilah). This research aims to analyze the implementation of zakat funds in the development of educational facilities and insfastructure in Jayapura Citry through the National  Zakat Amal Agency (BAZNAS) in Jayapura City. Zakat, as an Islamic financial instrument, has great potential to support improving the quality of education in areas that need it. This research uses a qualitative method with a case study approach, where data is collected through analysis of related documents. This research provides important insights into how zakat funds can be used effectively to improve the quality of education in areas in need, as well as challenges and solutions that can be applied to increase zakat participation and management.